Schädigungsmodell für die Hydroabrasionsbeanspruchung zur probabilistischen Lebensdauerprognose von Betonoberflächen im Wasserbau - Vogel, Michael (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2017)
Hydraulic structures are exposed to multifaceted exposures. Particular the hydro-abrasive wear of the concrete edge zones represents a key exposure. The knowledge about the abrasive mechanisms of concrete and its degradation process is still insufficient. Relating to the hydro-abrasive test method, the relevant material parameter and degradation model incomplete knowledge existed which was removed.